ANALISA STRUKTUR DAN PERFORMA IMPELLER POMPA SENTRIFUGAL DENGAN MENGGUNAKAN COMPUTATIONAL FLUID DYNAMIC AND FINITE ELEMENT METHOD - Gunawan Dwi Haryadi; Ismoyo Haryanto; I.M.W. Ekaputra; Rando Tungga Dewa; Deka Setyawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Centrifugal pumps are divided into two main components, namely the impeller and the volute. The impeller is a rotating pump component, while the volute is a stationary pump component. The current problem in the industrial world is that the pump capacity that operates is not in accordance with the written capacity so that the pump does not work optimally. In addition, the structural analysis of the pump is minimally carried out so that damage to the pump often occurs. To overcome this, it is necessary to analyze the performance and structure of the centrifugal pump design using computational fluid dynamics and static structural analysis methods on variations in the number of blades & impeller rotation speed. The results of the CFD analysis obtained are validated using existing product specifications and studies that have been carried out. The maximum value of the resulting von-mises stress is 20,238 Mpa, the maximum value of the resulting strain is 0.00010133, while the maximum total deformation value is 0.051984 mm. The three maximum values ​​occur in the variation of the 7 blade impeller with a rotational speed of 1800 rpm.